Reading Handbook Development Based on TOEIC For Balikpapan State Polytechnic Students (Research and Development Study) - Elisabeth Milaningrum; Masrul Huda (IJECA (International Journal of Education and Curriculum Application), 2021)
This research aims to develop the existing reading handbook that is related to the students' needs and students’ English proficiency at Balikpapan State Polytechnic. The research method used research and development (R & D) for developing a supplementary existing reading handbook based on TOEIC. The R & D study is divided into 2 stages: (1) exploration stage, consisting of library research, document analysis, and needs analysis. Based on the findings of the exploration stage, it can be concluded that: (a) the students have difficulty in analyzing the question pattern of completion and error recognition; (b) the students do not master the vocabularies of TOEIC reading comprehension ;(c) the students do not familiar with the context of TOEIC reading text; (d) the students have difficulty to analyze the pattern of TOEIC reading comprehension question; and (2) development stage, consisting of numerous steps aimed at designing  the supplementary existingreading handbook based on TOEIC : (a) designing prototype based on the result of exploration stage; (b) experts’ validation; (c) trying out the prototype; (d) final revision. The result shows that supplementary existing reading handbook based on TOEIC can help the students increase their TOEIC reading score and useful in their job field.